Implementasi Nilai-Nilai Islam dalam Pendidikan Anak Usia Dini: Membangun Karakter Islami dan Kemandirian Melalui Metode Pendidikan Terpadu - Mariana (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Early childhood education is a golden age for the formation of children's character and personality. Islamic education plays an important role in shaping Islamic character and independence in early childhood. The implementation of Muslim values in early childhood education can be done through integrated education methods. Integrated education methods are education methods that integrate various aspects of child development, both cognitive, affective, and psychomotor. This method has several advantages, including: More effective in developing children's potential in a holistic manner, More interesting and enjoyable for children, More relevant to the needs and development of children. The formation of Islamic character and independence in early childhood can be done through integrated education methods by integrating Islamic values into various learning activities. Some examples of learning activities that can be done include: Worship activities: Teach children about the procedures for worship, such as prayer, ablution, and fasting, Habit-forming activities: Habituate children to do good things, such as honesty, discipline, and helping others, Storytelling activities: Tell Islamic stories that can instill Islamic values in children, Play activities: Using games that can develop children's Islamic character and independence. The implementation of Muslim values in early childhood education through integrated education methods can be a solution to form Islamic character and independence in early childhood.